Quid facit cum psalterio Horatius? (Hier. ep. 22,29,7): Untersuchung zu Hieronymus' Umgang mit klassischen und biblischen Referenzen am Beispiel von Epistula 3 ad Rufinum. - Feichtinger, Barbara (Vigiliae Christianae, 2021)
Using the example of Epistula 3 Jerome's citation technique is analyzed in detail. For this purpose, a comprehensive classification grid of intertextual references is introduced for the first time, which allows a systematization of the narrative examination of citations and allusions. Thus, not only differences in the use of Bible verses and quotations of classics can be highlighted transparently but also a (radical) syntactic, structural, and semantic incorporation of biblical and classic pre-texts by Jerome's text can be substantiated. In stark contrast to former, rather negative verdicts on Jerome's "cento style" and semantic incoherences in his writing, this approach is capable of showing a high functionality and authority in Jerome's strategy of referencing, which shapes the narrative of the friendship letter not only aesthetically but also significantly helps to constitute its semantics.